Bài giảng Đồ án bê tông cốt thép dân dụng - Bộ môn Xây dựng dân dụng và công nghiệp (Trường Đại học Thủy Lợi, 2020)
http://catalog.tlu.edu.vn/exlibris/aleph/u22_2/alephe/www_f_eng/icon/ebook/lecturenote/24779.pdf